KAJIAN ESTETIKA DAN REALISME SOSIALIS TIGA PATUNG MONUMEN (PATUNG SELAMAT DATANG, PEMBEBASAN IRIAN BARAT DAN DIRGANTARA) ERA SOEKARNO DI JAKARTA - Pattiasina, Dianthus Louisa (Jurnal Ilmiah Widya, 2014)
The three sculptural monuments namely ‘Selamat Datang’ statue, ‘Pembebasan Irian Barat’ statue, and ‘Dirgantara’ statue in Jakarta, as the creation of the sculptor Edhi Sunarso which was initiated by Soekarno are considered as the initial growth of the Indonesian sculpture art history. These three pieces of sculptural monument considered to be affected by socialist realism concept, grown in the years of 60’s which was the concept of artistic creativity carried out by Partai Komunis Indonesia (PKI) and disseminated by Lembaga Kebudayaan Rakyat (LEKRA) and supported by the government at that time. The objective of this writing is to discuss: (1) the ideas and the sculptor of the three sculptural monuments; Selamat Datang statue, Pembebasan Irian Barat statue and Dirgantara statue (2) the assumptions regarding the influence of socialist realism against the three sculptural monuments in aesthetic forms of expression, (3) the constructions of the three statues related to the image quality of Indonesia. The conclusions are: (1) the sculptor Edhi Sunarso successfully embodies the idea of Bung Karno in aesthetic qualities as a form of expression (power of expression). (2) The strength as the visual concept on those three statues aesthetically shows and provides enrichment the specific form of expression in line with the purpose and the idea. (3) The constructions of the three statues as an artwork as an effort in accordance to support the idea of image equality for Indonesia which refers to national pride and was also as a symbol of national triumph which usually build in big cities of the world.